THE EFFECT OF HIGH TEMPERATURE ON THE POROSITY AND COMPRESSIVE STRENGTH ON THE CARBON FIBER REINFORCED LIGHTWEIGHT CONCRETE - Demirel, Bahar; Gonen, Tahir (Pamukkale Univ, 2008)
In this study, the effect of high temperature on the mechanical properties of the carbon fiber reinforced lightweight concrete with silica fume was investigated. With this aim, lightweight concrete samples were produced by using basaltic pumice (scoria) obtained from Elazig region. In addition, the samples produced with and without silica fume and carbon fiber. Silica fume was replaced 10 % by weight of cement and carbon fiber was added 0.5 % by weight of cement. Four different series of samples were prepared in order to observe the effect of high temperature on the physical and mechanical properties of both the lightweight concrete with and without silica fume and the lightweight concrete with and without carbon fiber. The specimens completed the 365 days curing period were exposed to 250, 500, 750 and 1000 degrees C for 1 hour. Porosity and compressive strength were determined and recorded after the specimens were cooled at the room temperature. In conclusion, it is determined that the losing of compressive strength in the specimens with silica fume is higher than the others. Relation of compressive strength-porosity is high out of 500-750 degrees C.
Keywords: High temperature; Carbon Fiber; Lightweight Concrete; Silica Fume; Pumice